Empirical models to predict rheological properties of fiber reinforced cementitious composites for 3D printing - Weng, Yiwei (2019)
3D printable construction materials need to be conveyed through a delivery system whilst possess certain flow resistance to ensure materials can sustain the weight of subsequent layers. To meet these requirements, material rheological properties should be optimized. In this study, factorial design was adopted to evaluate the influences of five variables (water-to-binder ratio, sand-to-binder ratio, fly ash-to-cement ratio, silica fume-to-cement ratio, and dosage of fiber) on material rheological properties (flow resistance, torque viscosity and thixotropy). Empirical models were established to predict rheological properties and were verified by experiment. Results imply that the increment of the dosage of fiber boosts all the rheological parameters, which are declined with the increment of water-to-binder ratio. Torque viscosity raises while flow resistance and thixotropy are decreased with the rise of fly ash-to-cement ratio. Conversely, the influence of silica fume-to-cement ratio shows an opposite trend on rheological properties as compared to that of fly ash-to-cement ratio. Flow resistance and torque viscosity are improved whilst thixotropy is declined if sand-to-binder ratio increases. Different formulations were adopted in printing test for verification and demonstration purpose via a robotic arm printing system in the end.